2021
DOI: 10.1007/s12035-021-02540-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipin1 Alleviates Autophagy Disorder in Sciatic Nerve and Improves Diabetic Peripheral Neuropathy

Abstract: Diabetic peripheral neuropathy (DPN) is a chronic complication of diabetes, and its exact pathogenesis remains unclear. Autophagy plays an important role in neurodegenerative diseases, ischemiareperfusion injury of nerve tissues, and nerve tissue injury repair. Lipin1 is a phosphatidic acid phosphatase enzyme that converts phosphatidic acid (PA) into diacylglycerol (DAG), a precursor of triacylglycerol and phospholipids which plays an important role in maintaining normal peripheral nerve conduction function. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In support of this idea, inhibiting DGAT and lipin1, a DG synthesizing enzyme, promotes axon regeneration in peripheral neurons by reducing TG/DG synthesis and stimulating phospholipid synthesis ( Yang et al, 2020 ). Furthermore, modulating DG levels in the sciatic nerve of STZ-treated rats confers neuroprotection and improves PN measures ( Wang et al, 2021 ). Future preclinical studies focused on nerve-specific TG/DG biology in the setting of dyslipidemia and metabolic dysfunction could facilitate the development of targeted interventions for the treatment of PN.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, inhibiting DGAT and lipin1, a DG synthesizing enzyme, promotes axon regeneration in peripheral neurons by reducing TG/DG synthesis and stimulating phospholipid synthesis ( Yang et al, 2020 ). Furthermore, modulating DG levels in the sciatic nerve of STZ-treated rats confers neuroprotection and improves PN measures ( Wang et al, 2021 ). Future preclinical studies focused on nerve-specific TG/DG biology in the setting of dyslipidemia and metabolic dysfunction could facilitate the development of targeted interventions for the treatment of PN.…”
Section: Discussionmentioning
confidence: 99%
“…DPN is mainly caused by microvascular lesions caused by metabolic abnormalities caused by hyperglycemia. Studies have shown that [16] the up-regulation of lipid in DPN rats improves the pathological changes of autophagy disorder and sciatic nerve, and the overexpression of lipin1 in RSC96 cells also significantly reduces the excessive autophagy activity and apoptosis caused by hyperglycemia. Therefore, it is speculated that Qianghuo-Yinchen pair may affect the metabolism and apoptosis of the body by regulating the lipid and atherosclerosis signaling pathways, and the signaling pathways of neurodegenerative diseases, so as to play a role in the treatment of DPN.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, these conditions predispose sciatic nerve damage that is mainly characterized by disordered myelin, axonal shrinkage, fibrosis, and inflammation. Recent work on damaged sciatic nerve induced by DPN showed a neuroprotective effect of lipin1, as a well-established enzyme to maintain normal conduction in peripheral nerve by modulating dysregulated autophagy and neutralizing the Schwann cell apoptosis ( Wang et al, 2021 ). This factor is diminished under diabetic conditions.…”
Section: Autophagy and Analgesiamentioning
confidence: 99%